Zero field PDD and TMR data for unflattened beams in conventional linacs: A tool for independent dose calculations. Issue 12 (December 2016) - Strolin, Silvia; Minosse, Silvia; D'Andrea, Marco; Fracchiolla, Francesco; Bruzzaniti, Vicente; Luppino, Stefano; Benassi, Marcello; Strigari, Lidia
Highlights: Analytical results based on Br.J.Supp.n.25 were obtained from PDDs of FFF beams. MC-based PDDs at different SSDs were in good agreement with analytical ones. Calculated and measured TPR 10 20 s values differ less than 1.5% on most field sizes. Br.J.Supp.n.25 can be used for FFF beams as independent dose calculation tool. Abstract: Purpose: To investigate the applicability of the formalism described in BJR supplement n.25 for Flattening Filter Free (FFF) beams in determining the zero-field tissue maximum ratio (TMR) for an independent calculation method of Percentage Depth Doses (PDDs) and relative dose factors (RDFs) at different experimental setups. Methods: Experimental PDDs for field size from 40 × 40 cm 2 to 2 × 2 cm 2 with Source Surface Distance (SSD) 100 cm were acquired. The normalized peak scatter factor for each square field was obtained by fitting experimental RDFs in water and collimator factors (CFs) in air. Maximum log-likelihood methods were used to extract fit parameters in competing models and the Bayesian Information Criterion was used to select the best one. In different experimental setups additional RDFs and TPR 10 20 s for field sizes other than reference field were measured and Monte Carlo simulations of PDDs at SSD 80 cm were carried out to validate the results. PDD agreements were evaluated by gamma analysis. Results: The BJR formalism allowed to predict the PDDs obtained with MC within 2%/2 mm at SSD 80 cm from 100% down to 50% of the maximum dose. The agreement between experimental TPR 10 20 s and RDFs values at SSD = 90 cm and BJR calculations were within 1% for field sizes greater than 5 × 5 cm 2 while it was within 3% for fields down to 2 × 2 cm 2 . Conclusions: BJR formalism can be used for FFF beams to predict PDD and RDF at different SSDs and can be used for independent MU calculations.